2015
DOI: 10.1111/ases.12154
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel obstruction caused by endometriosis in a postmenopausal woman

Abstract: We report a rare case of small bowel obstruction (SBO) caused by endometriosis in a postmenopausal woman. A 54-year-old postmenopausal woman presented with severe abdominal pain and vomiting. Before menopause, she sometimes had abdominal pain associated with menses. Axial multi-dimensional CT images revealed a SBO with small nodules near the terminal ileum. The obstruction was diagnosed as being caused by small bowel endometriosis. Curved planar reconstruction images showed a complicated obstruction of the sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Our review found 29 women (Table 1) with progressively increasing symptoms after menopause in whom endometriosis was diagnosed in the absence of HRT intake or an increased endogenous estrogen production. The symptoms are variable and comprise increasing pain with urinary symptoms [26], an asymptomatic cystic ovarian endometrioma or a cystic ovarian endometrioma with pain [27][28][29][30][31], a small bowel obstruction [32,33], a rectovaginal deep endometriosis [29,34], a sigmoid deep endometriosis [35], even a sigmoid obstruction more than 10 years after menopause [36], a deep endometriosis with progressive hydronefrosis [37], with renal failure [38] and with severe hypertension [39], urinary bleeding with an hydronephrosis and a polypoid intra-ureteral lesion [40], a vaginal endometriotic cyst [41], a lesion mimicking a bowel tumor [42], or an abdominal hemorrhage [43]. Some women were preoperatively suspected to have a cancer either an adenocarcinoma [44] or a disseminated ovarian cancer although during surgery only superficial endometriosis lesions together with bilaterally large endometriomas were found [45].…”
Section: A Systematic Review Of Clinically Progressive Postmenopausal Endometriosis Without Estrogen Intake or Increased Productionmentioning
confidence: 99%
“…Our review found 29 women (Table 1) with progressively increasing symptoms after menopause in whom endometriosis was diagnosed in the absence of HRT intake or an increased endogenous estrogen production. The symptoms are variable and comprise increasing pain with urinary symptoms [26], an asymptomatic cystic ovarian endometrioma or a cystic ovarian endometrioma with pain [27][28][29][30][31], a small bowel obstruction [32,33], a rectovaginal deep endometriosis [29,34], a sigmoid deep endometriosis [35], even a sigmoid obstruction more than 10 years after menopause [36], a deep endometriosis with progressive hydronefrosis [37], with renal failure [38] and with severe hypertension [39], urinary bleeding with an hydronephrosis and a polypoid intra-ureteral lesion [40], a vaginal endometriotic cyst [41], a lesion mimicking a bowel tumor [42], or an abdominal hemorrhage [43]. Some women were preoperatively suspected to have a cancer either an adenocarcinoma [44] or a disseminated ovarian cancer although during surgery only superficial endometriosis lesions together with bilaterally large endometriomas were found [45].…”
Section: A Systematic Review Of Clinically Progressive Postmenopausal Endometriosis Without Estrogen Intake or Increased Productionmentioning
confidence: 99%
“…Bowel obstruction due to endometriosis is a diagnosis usually made in young women of reproductive age. However, we identified six exceptions to that rule in postmenopausal females with acute bowel obstruction due to endometriosis [30][31][32][33][34][35] (Table 2). For 39 patients, the diagnostic workup in the emergency room included performing a colonoscopy.…”
Section: Patients' Characteristicsmentioning
confidence: 96%
“…The mean age of patients diagnosed with ileal occlusions (41 cases) [26,34,35, was 38.71, with a minimum of 22 and a maximum of 54. Conservative treatment of ileal obstruction was first attempted in seven patients [26,34,40,53,64,67,72], five of whom were subsequently managed after a few days with laparoscopic surgery. Two of those interventions were single-incision laparoscopic surgeries, both of which were performed in Japan in 2021 and 2015 [34,40].…”
Section: Ileal Obstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…transverse colon iron deficiency anemia; Blood in the stool Deval B (2002) [15] colon endometrioma pelvic pain, vaginal discharge, constipation, and a weight loss of 30 kg progressing over a 6month period Goldsmith, P. J. (2009) [18] liver right upper quadrant pain and a cystic liver mass Verbeke, C (1996) [35] liver right epigastric pain Abdallah A.A (2016) [26] gastric endometriosis epigastric pain, left loin pain, nausea Izuishi K (2015) [20] small bowel severe abdominal pain and vomiting Klenov VE (2015) [21] invasive pelvic endometriosis vaginal bleeding, hematuria Petros JG (1992) [22] colonic endometriosis (two cases) colonic obstruction Kempers (1960) [23] intestinal (8 cases) pain Popoutchi P (2008) [24] sigmoid, rectum hematochezia and tenesmus, pelvic pain, liquid feces, pelvic pain Choi JK (2020) [25] primary cutaneous endometriosis of the navel bump in the navel, umbilical pain Abdallah A.A (2016) [26] gastric endometriosis epigastric pain, left loin pain, nausea al-Izzi MS (1989) [27] bladder wall hematuria Plodeck V (2016) [28] pancreas left upper quadrant pain Sarpietro (2022) [29] vulva vulvar lump Corazza M [30] vulva blackish macule and a small central ulcer…”
Section: Snyder Bm (2018) [1]mentioning
confidence: 99%